Possible Association of Female-Pattern Hair Loss with Alteration in Serum 25-Hydroxyvitamin D Levels - Raef Hailat, Hira Mughal, Tooba Malik, Afshan Sagheer, Asma Javed, Quratulain Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Most women who experience diffuse hair loss suffer from female-pattern hair loss (FPHL). Several mechanisms other than androgen have been suggested as contributing to the process. Serum 25-hydroxy vitamin D [25-(OH) D] has been associated with other hair disorders. The present study aimed to assess the female-pattern hair loss possible association with variation in serum 25-hydroxyvitamin D levels. Patients and Methods: This case-control study was conducted on 72 FPHL diagnosed female patients attending dermatology department of Tertiary Care Hospitals in Jamshoro and Karachi from November 2021 to October 2022. Females aged 18-40 years with skin prototypes III and IV were enrolled. About 72 healthy females were considered as control group. Study protocol was approved by the institutional research and ethical committee. Careful history, socioeconomic status, FPHL family history, menstrual history, and drug intake were recorded from cases and control. Patients were classified as having stage I, II, or III FPHL based on a clinical evaluation of the pattern of hair loss using Ludwig’s scale. 25-OHD levels over a period of 4 months were measured to minimize seasonal bias. Females with 25-OHD levels <20 ng/ml were deficient, insufficient 21–29 ng/ml, sufficient >30 ng/ml, and intoxication >150 ng/ml. SPSS version 26 was used for data analysis. Results: The overall mean age was 28.6±2.4 years. Age-wise distribution of patients were as follows: 9 (12.5%) in 18-25 years, 24 (33.3%) in 26-30 years, 21 (29.2%) in 31-35 years, and 18 (25%) 36-40 years. Serum 25-(OH) D levels in FPHL patients were significantly lower (15.4 ± 8.25 ng/ml) than in controls (46.42 ± 19.92 ng/ml). The mean vitamin D level did not differ significantly between patients with and without family history (14.46 ± 8.62 and 13.9 ± 8.24 ng/ml, respectively. The mean vitamin D level differed significantly between the three Ludwig’s degrees (13.15 ± 8.49, 14.23 ± 6.74, and 24.9 ± 6.42 ng/ml, respectively): between degrees I and III, as well as between degrees II and III. Conclusion: The present study showed that hair loss varied significantly across all age groups. Premenopausal women with vitamin D deficiency have higher rates of hair loss, which is most profound in the age groups 26-30, followed by 25-30. Furthermore, changes in serum 25-(OH) D levels, whether deficient or sufficient, may play a role in the etiology of FPHL. Keywords: Female Pattern Hair Loss (FPHL), Vitamin D, Serum 25-hydroxy vitamin D